Analysis of Planned Flood Discharge in the Grompol Watershed - Wulandari, Aprilia Indah; Mulyandari, Erni; Yuono, Teguh (Syntax Corporation, 2024)
The Grompol watershed is one of the sub-watersheds of Bengawan Solo located in Karanganyar Regency and Sragen Regency. When the intensity of rainfall is high, the area downstream of the Grompol River often floods to cause many losses. Therefore, analyzing the planned flood discharge as a reference in flood control efforts is necessary. This study aims to identify the most common problems in the Grompol River flow, identify flood points in the Grompol River and its countermeasures, analyze the size of the Grompol Watershed using QGIS 3.10.6 Software, and calculate the amount of planned flood discharge in the Grompol Watershed. The method in this study is the Nakayasu Synthesis Unit Hydrograph Method, with a repeat period of 25 years. The analysis stage begins with conducting a location survey and interviews and then conducting a planned flood discharge analysis. Based on the results of the research, it was found that the problems that occur a lot in the Grompol River flow are sediment, organic waste, and inorganic waste, as well as streams that have been flooded at 4 points out of 31 survey locations, namely in the settlements around the Gedangan Lor Bridge, Gading Grompol, Gantung Kedusan, and Pringanom, where flood control efforts are dominated in the form of community service, an area of the Grompol watershed is obtained using Software QGIS 3.10.6 is 164,95 km2 while for flood discharge for the 25-year recurrence period using the Nakayasu Synthetic Unit Hydrograph Method of 623,32 m3/s.